Quinupristin-Dalfopristin Resistance among Gram-Positive Bacteria in Taiwan - Luh, Kwen-Tay (American Society for Microbiology, 2000)
To understand quinupristin-dalfopristin resistance among clinical isolates of gram-positive bacteria in Taiwan, where this agent is not yet available for clinical use, we evaluated 1,287 nonduplicate isolates recovered from January 1996 to December 1999 for in vitro susceptibility to quinupristin-dalfopristin and other newer antimicrobial agents. All methicillin-susceptible Staphylococcus aureus (MSSA) isolates were susceptible to quinupristin-dalfopristin. High rates of nonsusceptibility to quinupristin-dalfopristin (MICs, ≥2 μg/ml) were demonstrated for the following organisms: methicillin-resistant S. aureus (MRSA) (31%), coagulase-negative staphylococci (CoNS) (16%), Streptococcus pneumoniae (8%), viridans group streptococci (51%), vancomycin-susceptible enterococci (85%), vancomycin-resistant Enterococcus faecalis (100%), vancomycin-resistant Enterococcus faecium (66%), Leuconostoc spp. (100%), Lactobacillus spp. (50%), and Pediococcus spp. (87%). All isolates of MSSA, MRSA, S. pneumoniae, and viridans group streptococci were susceptible to vancomycin and teicoplanin. The rates of nonsusceptibility to vancomycin and teicoplanin were 5 and 7%, respectively, for CoNS, ranging from 12 and 18% for S. simulans to 0 and 0% for S. cohnii and S. auricularis. Moxifloxacin and trovafloxacin had good activities against these isolates except for ciprofloxacin-resistant vancomycin-resistant enterococci and methicillin-resistant staphylococci. In Taiwan, virginiamycin has been used in animal husbandry for more than 20 years, which may contribute to the high rates of quinupristin-dalfopristin resistance.